Nanoparticle modified epoxy heavy anti-corrosion coating and preparation method thereof

By combining homemade nano-modified resin with epoxy resin and combining amine-based curing agents, nanoparticle modified epoxy coatings with excellent adhesion and weather resistance are prepared, which solves the decline in performance and high construction costs in traditional coating processes. The problem of the long-life anti-corrosion performance of marine wind power equipment has been improved and environmentally friendly coating solutions.

CN119192956AActive Publication Date: 2024-12-27IANGSU JINLING SPECIAL PAINT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411413911.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-27
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the traditional marine fan tower coating process, zinc-rich primer performance is degraded, the construction procedures are complex and costly, and it is difficult to meet the requirements of long life and daily maintenance. It is necessary to develop long life heavy corrosion primer and weather-resistant topcoat to improve corrosion protection. Performance and reduce environmental impact.

Method used

The nanostructures are prepared by combining homemade nanomodified resin with epoxy resin, and the hydrosilicon addition of phosphate esters and alkoxysilane monomers are formed to form a stable three-dimensional network structure, combined with hydrolysis and condensation of epoxysiloxane monomers, and nanostructures are prepared. Particle modified epoxy heavy corrosion protection coating, and amine-based curing agent is added to improve adhesion and weather resistance.

Benefits of technology

Significantly improves the adhesion of the coating, salt spray resistance, salt water resistance and humidity resistance, extends service life, reduces construction costs, and is suitable for corrosion protection of marine wind power equipment in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005078812940000021
    Figure BDA0005078812940000021
  • Figure BDA0005078812940000031
    Figure BDA0005078812940000031
  • Figure BDA0005078812940000081
    Figure BDA0005078812940000081
Patent Text Reader

Abstract

The invention discloses a nano particle modified epoxy heavy anti-corrosion coating. Self-made nano modified resin and epoxy resin are compounded to serve as main film-forming resin, pigment filler and auxiliaries are added to prepare a component A, an amine curing agent is a component B, and the ratio of the amount of substance of active epoxy of the component A to the amount of substance of active hydrogen of the component B is 1: (0.7-1.3). The coating prepared by the invention contains a P-OH structure, so that the coating and a metal base material are combined through chemical bonds generated by a phosphating reaction, the adhesive force of the coating is greatly improved, and the compactness of the coating is improved due to introduction of nano ions; therefore, the nano particle modified epoxy coating has excellent adhesive force, salt mist resistance, brine resistance, damp heat resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fine chemical industry, and in particular to a nano-particle modified epoxy heavy-duty anti-corrosion coating and a preparation method thereof. Background Art

[0002] With the rapid increase in global energy demand, the development and utilization of new clean energy has received more and more attention, among which the development of offshore wind power is quite rapid. Since the environment of offshore wind turbines is a highly corrosive environment, and in recent years, with the continuous increase in the power of wind turbines, the size of the equipment has become larger, the investment has become higher, and the maintenance difficulty has increased, which puts higher requirements on the anti-corrosion coating of offshore wind turbine towers.

[0003] The traditional coating process for offshore wind turbine towers is zinc-rich primer / epoxy micaceous iron intermediate paint / polyurethane topcoat. Although this technology can meet the anti-corrosion requirements to a certain extent, it also has some disadvantages. For example, the performance of the zinc-rich primer will decline with the extension of service time, and its service life is difficult to meet the applicable requirements of wind power equipment. Moreover, the construction procedure of the traditional three-coat coating system is complicated, the construction cost is high, and it is inconvenient for daily maintenance and repair. At present, there is an urgent need for a long-life heavy-duty anti-corrosion primer and a long-life weather-resistant topcoat to ensure the protective life of the coating and reduce the construction cost of the coating, providing technical support for the long-term development of the wind power industry. Therefore, it is very urgent to replace the zinc-rich primer with an epoxy micaceous iron intermediate paint.

[0004] To overcome the above shortcomings, researchers are exploring new environmentally friendly coatings, hoping to improve the corrosion resistance of offshore wind turbine towers, extend their service life, and reduce the impact on the environment. Summary of the invention

[0005] Purpose of the invention: In view of the shortcomings of the prior art, the research purpose of the present invention is to prepare a nanoparticle-modified epoxy heavy-duty anti-corrosion coating, which has excellent adhesion, resistance to salt spray, resistance to salt water, resistance to moisture and heat, etc.

[0006] Technical solution: The present invention provides a nanoparticle-modified epoxy heavy-duty anti-corrosion coating, which comprises a component A and a component B. The component A is prepared by compounding a homemade nano-modified resin with an epoxy resin as the main film-forming resin, adding pigments, fillers and additives, and an amine curing agent is the component B; the amount of active epoxy in the component A to the amount of active hydrogen in the component B is 1:(0.7-1.3);

[0007] The self-made nano-modified resin adopts phosphate containing double bonds and P-OH structures and alkoxysilane monomer containing Si-H bonds to obtain phosphate-modified alkoxysilane monomer through hydrosilylation, and the monomer is hydrolyzed and condensed with siloxane monomer and epoxy-containing siloxane monomer to prepare nanoparticles.

[0008] Specifically, the weight content of each component in component A is:

[0009]

[0010] Specifically, the epoxy resin is a bisphenol A epoxy resin with an epoxy equivalent of 154 to 600; more specifically, it is selected from at least one of E51, E44, and E20.

[0011] Specifically, the nano-modified resin is obtained by the following method: tetrahydrofuran, double-bond-containing phosphate, and Si-H bond-containing alkoxysilane monomer are added to a reactor, reacted at room temperature for 2-5 hours, then heated to a reflux state, kept warm for 2-6 hours, cooled, and then distilled under reduced pressure to remove tetrahydrofuran; after removing tetrahydrofuran, siloxane monomer and deionized water are added, stirred for 10-60 minutes, and then a catalyst is added, stirred for 1-3 hours, until the system is clear and transparent, siloxane monomer containing an epoxy group is added, the temperature is raised to reflux for at least 2 hours, by-product ethanol in the system is removed by distillation under reduced pressure, and cooled to room temperature to prepare the nano-modified resin.

[0012] Preferably, tetrahydrofuran, double-bond-containing phosphate, and Si-H-bond-containing alkoxysilane monomer are added to the reactor at one time, reacted at room temperature for 3 hours, then heated to reflux state, kept warm for 4 hours, cooled, and then distilled under reduced pressure to remove tetrahydrofuran; after removing tetrahydrofuran, siloxane monomer and deionized water are added, stirred for 30 minutes, and then a catalyst is added, stirred for 2 hours, and a siloxane monomer containing an epoxy group is added until the system becomes clear and transparent, the temperature is raised to reflux for at least 2 hours, and the by-product ethanol in the system is distilled under reduced pressure to remove it, and cooled to room temperature to prepare a nano-modified resin.

[0013] Specifically, the content of each component of the nano-modified resin is:

[0014]

[0015] Specifically, the double-bonded phosphate ester is selected from at least one of allyl methyl phosphate, allyl ethyl phosphate, and allyl propyl phosphate. Through its double bond, it undergoes addition reaction with an alkoxysilane monomer containing a Si-H bond to form a stable three-dimensional network structure, thereby improving the hardness, strength, and chemical corrosion resistance of the material. In the present invention, allyl propyl phosphate, or allyl methyl phosphate and allyl propyl phosphate are preferred.

[0016] Specifically, the alkoxysilane monomer containing Si-H bonds is selected from at least one of triethoxysilane, trimethoxysilane, methyldiethoxysilane and methyldimethoxysilane. As the basic skeleton building unit of the resin. It reacts with a double-bonded phosphate to form a siloxane network, which increases the flexibility and adhesion of the material and improves the thermal stability and weather resistance of the resin. In the present invention, methyldiethoxysilane and methyldimethoxysilane, or triethoxysilane and trimethoxysilane are preferred.

[0017] Specifically, the siloxane monomer is selected from at least one of methyltriethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, phenylmethyldimethoxysilane and phenylmethyldiethoxysilane. Si-O-Si bonds are formed by hydrolysis and condensation reaction to build a tighter siloxane network, thereby improving the mechanical strength, heat resistance and chemical resistance of the material. In the present invention, methyltriethoxysilane, dimethyldimethoxysilane and phenylmethyldiethoxysilane, or methyltrimethoxysilane is preferred.

[0018] Specifically, the epoxy-containing siloxane monomer is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltriethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldiethoxysilane, and γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane. The epoxy group can react with a variety of functional groups, such as hydroxyl, carboxyl, etc., so as to improve the compatibility and adhesion of the resin with other materials, and also enhance the chemical resistance and electrical insulation of the material. In the present invention, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane, or γ-(2,3-epoxypropoxy)propyltrimethoxysilane are preferred.

[0019] Specifically, the catalyst is selected from at least one of hydrochloric acid, sulfuric acid, acetic acid, and nitric acid. The selection of the catalyst (such as hydrochloric acid, sulfuric acid, acetic acid, and nitric acid) can significantly accelerate the hydrolysis and condensation reaction rate of the siloxane monomer, shorten the preparation cycle, and ensure the high efficiency and controllability of the reaction. In the present invention, acetic acid or sulfuric acid is preferred.

[0020] Specifically, the pigment filler is selected according to the final color requirements of the coating, and is selected from at least one of titanium dioxide, carbon black, iron red, phthalocyanine blue, cobalt blue, chrome green, kaolin, talc, silica powder, mica powder, and micaceous iron powder.

[0021] Specifically, the anti-corrosion filler is selected from at least one of zinc phosphate, strontium phosphate, aluminum tripolyphosphate, and molybdate.

[0022] Specifically, the solvent is selected from at least one of xylene, butyl acetate, cyclohexanone and butanol.

[0023] Specifically, the auxiliary agent is selected from at least one of polyamide wax, fumed silica, organic bentonite, BYK-A530, BYK-A525, BYK-A535, BYK-333, and wax powder.

[0024] Specifically, the B component is selected from at least one of phenolic amine, phenolic amide, polyamide, alicyclic amine and fatty amine.

[0025] The present invention also provides a method for preparing the nanoparticle modified epoxy heavy anti-corrosion coating: weighing epoxy resin, nano-modified resin, pigment filler, anti-corrosion filler, solvent and additive into a container in sequence, mixing them evenly and then grinding them, filtering and packaging them after testing the fineness to be less than 50 μm.

[0026] Beneficial effects: The present invention adopts self-made nano-modified resin and epoxy resin to compound, and amine substances are used as curing agents to prepare coatings. The prepared coatings contain P-OH structures, so that the coatings and metal substrates are chemically bonded through phosphating reactions, which greatly improves the adhesion of the coatings. The introduction of nano-ions improves the density of the coatings. Therefore, the epoxy coatings modified by nano-particles have excellent adhesion, salt spray resistance, salt water resistance, moisture and heat resistance and other properties.

[0027] The nanoparticle-modified epoxy heavy-duty anti-corrosion coating prepared by the present invention has excellent adhesion (greater than or equal to 15Mpa), and properties such as resistance to salt spray for 5000 hours, resistance to salt water for 5000 hours, and resistance to damp heat for 5000 hours. DETAILED DESCRIPTION

[0028] The following are embodiments to illustrate the scheme of the present invention in detail, but the protection scope of the present invention is not limited to the embodiments.

[0029] Example 1

[0030] 10.00 g of tetrahydrofuran, 35.00 g of allyl phosphate monomethyl ester and 15.00 g of triethoxysilane were added into the reactor at one time, and the mixture was reacted at room temperature for 3 hours. The temperature was then raised to reflux state, and the mixture was kept warm for 4 hours before being cooled down. The tetrahydrofuran was then removed by vacuum distillation. After the tetrahydrofuran was removed, 15.00 g of methyltriethoxysilane and 5.00 g of deionized water were added, stirred for 30 minutes, 0.01 g of hydrochloric acid was added, and stirred for 2 hours. After the system became clear and transparent, 19.99 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added, the temperature was raised to reflux state for reaction for 3.5 hours, the by-product ethanol in the system was removed by vacuum distillation, and the system was cooled to room temperature to prepare nano-modified resin C-1.

[0031] Example 2

[0032] 20.00 g of tetrahydrofuran, 15.00 g of allyl monoethyl phosphate, 10.00 g of allyl monopropyl phosphate, 18.90 g of trimethoxysilane and 10.0 g of methyldiethoxysilane were added into the reactor at once, reacted at room temperature for 3 h, then heated to reflux state, kept warm for 4 h and cooled, and then the tetrahydrofuran was removed by vacuum distillation; after removing the tetrahydrofuran, 10.00 g of methyltrimethoxysilane, 5.00 g of phenyltriethoxysilane and 1.00 g of deionized water were added, stirred for 30 min, 0.10 g of nitric acid was added, stirred for 2 h, 5.00 g of γ-(2,3-epoxypropoxy)propyltriethoxysilane and 5.00 g of γ-(2,3-epoxypropoxy)propylmethyldiethoxysilane were added until the system was clear and transparent, the temperature was raised to reflux for reaction for 2.5 h, the by-product ethanol in the system was removed by vacuum distillation, and the system was cooled to room temperature to prepare nano-modified resin C-2.

[0033] Example 3

[0034] 14.70 g of tetrahydrofuran, 25.00 g of allyl monopropyl phosphate, 10.00 g of methyldiethoxysilane and 5.00 g of methyldimethoxysilane were added to the reactor at one time, and the mixture was reacted at room temperature for 3 h, then the temperature was raised to reflux state, and the mixture was kept warm for 4 h before cooling down. The tetrahydrofuran was then removed by vacuum distillation. After the tetrahydrofuran was removed, 20.00 g of methyltriethoxysilane, 5.00 g of dimethyldimethoxysilane, 5.00 g of phenylmethyldiethoxysilane and 5.00 g of deionized water were added, and the mixture was stirred for 30 min, followed by 0.30 g of acetic acid, and the mixture was stirred for 2 h. After the system became clear, 5.0 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 5.0 g of γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane were added, the temperature was raised to reflux state for reaction for 2 h, the by-product ethanol in the system was removed by vacuum distillation, and the system was cooled to room temperature to prepare nano-modified resin C-3.

[0035] Example 4

[0036] 10.00 g of tetrahydrofuran, 11.90 g of allyl monomethyl phosphate, 20.00 g of allyl monopropyl phosphate, 20.00 g of triethoxysilane and 10.00 g of trimethoxysilane were added into the reactor at once, reacted at room temperature for 3 hours, then heated to reflux state, kept warm for 4 hours and then cooled, and then the tetrahydrofuran was removed by vacuum distillation; after removing the tetrahydrofuran, 15.00 g of methyltrimethoxysilane and 3.00 g of deionized water were added, stirred for 30 minutes, and then 0.1 g of sulfuric acid was added and stirred for 2 hours. After the system became clear and transparent, 10.00 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added, the temperature was raised to reflux for reaction for 3 hours, the by-product ethanol in the system was removed by vacuum distillation, and the system was cooled to room temperature to prepare nano-modified resin C-4.

[0037] Example 5

[0038] Weigh 20.0g E51, 20.0g E44, 15.0g C-1 nano-modified resin, 3.0g titanium dioxide, 5.0g kaolin, 5.0g silica powder, 7.0g mica powder, 5.0g zinc phosphate, 7.0g strontium phosphate, 5.0g xylene, 5.0g butanol solvent, 1.0g polyamide wax, 0.2 fumed silica, 0.8g organic bentonite, 0.5g BYK-A530 and 0.5g BYK-333 into a container, mix well and grind. Test the fineness to be less than 50μm and filter and package to obtain A-1.

[0039] Example 6

[0040] Weigh 20.0g E44, 15.0g C-2, 10.0g C-3 nano-modified resin, 3.0g iron red, 2.0g chrome green, 10.0g kaolin, 8.0g talc, 7.0g silica powder, 10.0g iron powder, 5.0g aluminum tripolyphosphate, 6.5g butyl acetate, 3.0g butanol, 0.1g organic bentonite and 0.4g wax powder additive into a container, mix well and grind. Test the fineness to be less than 50μm and filter and package to obtain A-2.

[0041] Example 7

[0042] Weigh 18.0g E51, 10.0g E20, 15.0g C-4 nano-modified resin, 1.0g carbon black, 2.0g phthalocyanine blue, 4.0g talc, 7.0g silica powder, 11.0g mica powder, 10.0g aluminum tripolyphosphate, 15.0g molybdate, 4.0g cyclohexanone, 1.0g butanol, 0.5g organic bentonite, 0.5BYK-A530, 0.5g BYK-333 and 0.5g wax powder additive into a container, mix well and grind. Test the fineness to be less than 50μm and filter and package to obtain A-3.

[0043] Example 8

[0044] Weigh 30.0g E44, 10.0g C-1, 10.0g C-3 nano-modified resin, 8.5g titanium dioxide, 2.0g talc, 5.0g mica powder, 13.0g micaceous iron powder, 5.0g zinc phosphate, 5.0g molybdate, 7.0g xylene, 3.0g butanol, 0.5g fumed silica, 0.5g BYK-333 and 0.5g wax powder into a container, mix well and grind. Test the fineness to be less than 50μm and filter and package to obtain A-4.

[0045] A-1 to A-4 were used to prepare coatings with phenolic amine curing agent NX-2015 and phenolic amide curing agent LITE3100 respectively for testing, but the curing agent is not limited to a specific brand of a certain company.

[0046]

[0047]

[0048] The present invention prepares a nanoparticle modified epoxy heavy-duty anti-corrosion coating. The coating prepared by the coating has good adhesion, salt spray resistance and salt water resistance. The actual measured time of the salt spray and salt water resistance of the coating is 5000h, which does not mean that 5000h is its upper limit.

[0049] Comparative Example 1

[0050] Component A: substantially the same as Example 8, except that the nano-modified resin is replaced with a common commercially available resin to obtain Ad.

[0051] Component B: NX-2015 and LITE3100 are used respectively.

[0052]

[0053] It can be seen from comparative tests that the coating obtained by the method of the present invention has a better service life, especially in harsh environments.

[0054] The above description is only a preferred embodiment of the present application and is not intended to limit the present application.

Claims

1. A nanoparticle modified epoxy heavy-duty anti-corrosion coating, characterized in that: The coating comprises component A and component B, wherein a self-made nano-modified resin and an epoxy resin are compounded as the main film-forming resin, and pigments, fillers and additives are added to prepare component A, and an amine curing agent is component B; the amount of active epoxy in component A to the amount of active hydrogen in component B is 1:(0.7-1.3); The self-made nano-modified resin adopts phosphate containing double bonds and P-OH structures and alkoxysilane monomer containing Si-H bonds to obtain phosphate-modified alkoxysilane monomer through hydrosilylation, and the monomer is hydrolyzed and condensed with siloxane monomer and epoxy-containing siloxane monomer to prepare nanoparticles.

2. The nanoparticle-modified epoxy heavy-duty anti-corrosion coating according to claim 1, characterized in that: Weight content of each component in component A:

3. The nanoparticle-modified epoxy heavy-duty anti-corrosion coating according to claim 1, characterized in that: The epoxy resin is a bisphenol A type epoxy resin with an epoxy equivalent of 154 to 600; and is selected from at least one of E51, E44 and E20.

4. The nanoparticle-modified epoxy heavy-duty anti-corrosion coating according to claim 1, characterized in that: Tetrahydrofuran, double-bond phosphate, and Si-H bond-containing alkoxysilane monomer are added to a reactor, reacted at room temperature for 2-5 hours, then heated to a reflux state, kept warm for 2-6 hours, cooled, and then distilled under reduced pressure to remove tetrahydrofuran; after removing tetrahydrofuran, siloxane monomer and deionized water are added, stirred for 10-60 minutes, and then a catalyst is added, stirred for 1-3 hours, and a siloxane monomer containing an epoxy group is added until the system becomes clear and transparent, the temperature is raised to reflux for at least 2 hours, by-product ethanol in the system is removed by distillation under reduced pressure, and cooled to room temperature to prepare a nano-modified resin.

5. The nanoparticle-modified epoxy heavy-duty anti-corrosion coating according to claim 1, characterized in that: The content of each component of the nano-modified resin:

6. The nanoparticle-modified epoxy heavy-duty anti-corrosion coating according to claim 4, characterized in that: The double-bond-containing phosphate is selected from at least one of allyl phosphate monomethyl ester, allyl phosphate monoethyl ester, and allyl phosphate monopropyl ester; The alkoxysilane monomer containing Si-H bonds is selected from at least one of triethoxysilane, trimethoxysilane, methyldiethoxysilane and methyldimethoxysilane; The siloxane monomer is selected from at least one of methyltriethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, phenylmethyldimethoxysilane and phenylmethyldiethoxysilane; The epoxy-containing siloxane monomer is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltriethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldiethoxysilane, and γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane; The catalyst is selected from at least one of hydrochloric acid, sulfuric acid, acetic acid and nitric acid.

7. The nanoparticle-modified epoxy heavy-duty anti-corrosion coating according to claim 1, characterized in that: The pigment filler is selected from at least one of titanium dioxide, carbon black, iron red, phthalocyanine blue, cobalt blue, chrome green, kaolin, talcum powder, silica powder, mica powder, and micaceous iron powder; the anti-corrosion filler is selected from at least one of zinc phosphate, strontium phosphate, aluminum tripolyphosphate, and molybdate.

8. The nanoparticle modified epoxy heavy duty anti-corrosion coating according to claim 1, characterized in that The solvent is selected from at least one of xylene, butyl acetate, cyclohexanone and butanol; the auxiliary agent is selected from at least one of polyamide wax, fumed silica, organic bentonite, BYK-A530, BYK-A525, BYK-A535, BYK-333 and wax powder.

9. The nanoparticle-modified epoxy heavy-duty anti-corrosion coating according to claim 1, characterized in that: The B component is selected from at least one of phenolic amine, phenolic amide, polyamide, alicyclic amine and fatty amine.

10. The method for preparing the nanoparticle modified epoxy heavy-duty anticorrosion coating according to claim 1, characterized in that: Weigh epoxy resin, nano-modified resin, pigments and fillers, anti-corrosion fillers, solvents and additives into a container in sequence, mix them evenly and grind them. Test the fineness to be less than 50 μm and filter and package them.

Citation Information

Patent Citations

  • Modified epoxy resin powder coating with high adhesive force

    CN111925728A

  • Graphene-based composite fabric and electric heating tablecloth

    CN117488561A

  • Organic-inorganic hybrid resin that consisting epoxysilylphopshate polymer attached melamine functional group and incombustible paint compositions using the same

    KR101941460B1